PSYCHOLOGICAL ASPECTS OF PARENTAL RESPONSIBILITY IN CHILD EDUCATION - Alimova Nargiza Usmanovna (Journal of Learning on History and Social Sciences, 2024)
The article provides information on the influence of the family and relationships in it on the upbringing of children, as well as on the role of parents in the upbringing of children.